2016
DOI: 10.1186/s12906-016-1452-y
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro alpha amylase inhibitory activity of the leaf extracts of Adenanthera pavonina

Abstract: BackgroundDiabetes has caused a major burden to the health sector in the developing countries and has shown an increasing trend among the urban population. It is estimated that most patients are with type II diabetes which could be easily treated with dietary changes, exercise, and medication. Sri Lanka carries a long history ayurvedic medicine where it uses the plant for treating many diseases. Therefore it is important to screen medicinal plants scientifically so they could be used safely and effectively in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 10 publications
1
112
0
Order By: Relevance
“…The IC 50 value of acarbose was calculated from the dose-response curves (not given in this paper). The results indicated that the IC 50 value of acarbose was 20  μ g/mL, which was close to the value reported by Wickramaratne et al [8]. Therefore, the concentration of MT was set by taking the ratio between 100 mg of one dose of acarbose and 50 mg of one dose of MT.…”
Section: Methodssupporting
confidence: 82%
“…The IC 50 value of acarbose was calculated from the dose-response curves (not given in this paper). The results indicated that the IC 50 value of acarbose was 20  μ g/mL, which was close to the value reported by Wickramaratne et al [8]. Therefore, the concentration of MT was set by taking the ratio between 100 mg of one dose of acarbose and 50 mg of one dose of MT.…”
Section: Methodssupporting
confidence: 82%
“…The data obtained suggest that antioxidant activity could be related to the sulfation degree and probably the mechanism of action associated with the intrinsic hydrogen-donating ability of sulfate groups. Wickramaratne et al (2016) demonstrated the antioxidant activity by DPPH scavenging property, and the total phenolic content of different solvent extracts of A. pavonina leaves. The EtOAc fraction of A. pavonina leaves showed the highest total phenolic content (34.…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…Zeid et al (2012) reported its use as a tonic. These reports of traditional use were most common in Asian countries (Wickramaratne et al, 2016;Koodalingam et al, 2015;Dholvitayakhun et al, 2012;Arshad et al, 2010).…”
Section: Ethnomedicinal Usementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] In this study, the existence and contents of ten flavonoids were analyzed in the extract of lotus leaf. Centrifugal ultrafiltration combined with high performance liquid chromatography (HPLC) was performed for the screening and analysis of alpha-amylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%